IMPLEMENTASI SEKOLAH ADIWIYATA DI SD NEGERI SERAYU YOGYAKARTA - Aprilia Permata Sari (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2021)
ABSTRACTÂ This study aims to describe the implementation of adiwiyata school at SD Negeri Serayu Yogyakarta which includes 3 components of the Movement for Care and Culture of the Environment at Schools (PBLHS). This research is a qualitative research. Collecting data used observation, interview, and documentation techniques. The research subjects were the principal, adiwiyata teams, class teachers, and students. The data obtained were analyzed using qualitative descriptive analysis techniques. Examination of the validity of research data using triangulation techniques and triangulation of sources. The results research on the implementation of adiwiyata schools in SD Negeri Serayu showed that: (1) The PBLHS Movement Planning was prepared based on the School Self-Evaluation Report (EDS) and the results of the Identification of Environmental Potentials and Problems (IPMLH) by involving various parties, namely the school principal, the board of educators, and school Committee. The One KTSP document contains the PBLHS Movement and the teacher includes the implementation of PRLH into the RPP; (2) The implementation of the PBLHS Movement has been carried out through learning, extracurricular and self-accustoming that has been integrated into the Application of Environmentally Friendly Behavior (PRLH), the application of PRLH for the community, establishing work and communication networks, publication of the PBLHS Movement, forming and empowering Adiwiyata Cadres; (3) Monitoring & Evaluation of the PBLHS Movement was carried out by involving the principal, adiwiyata team, teachers and students; (4) Supporting factors and inhibiting factors. The supporting factor was the motivation of each individual to protect the environment and the inhibiting factor was the difference in commitment and lack of communication. The implementation of Adiwiyata School at SD Negeri Serayu Yogyakarta was conducted well based on P.53/Menlhk/Setjen/Kum.1/9/2019 which covers the planning, implementation, and monitoring & evaluation of the PBLHS Movement.Keywords: Adiwiyata School, PBLHS Movement, PRLH Implementation